Determinants of Adaptation during COVID-19 Pandemic by Rural Households in Cooch Behar District of West Bengal (Indian Journal of Extension Education, 2022)
The COVID-19 pandemic has led to loss of human life and presented an unprecedented challenge to public health and food systems. The study was conducted to assess the factors in terms of livelihood profile determining awareness and adaptation level. Using random sampling procedure, data were collected from 80 farmers from four villages under two blocks of Coochbehar district in 2021. Altogether eleven variables i.e., age, education, information availability, social participation, quality of common facilities services, mean distance of common facility services, economic status, expenditure during pandemic, net landholding, number of migrants in family and duration of migration explain 46.9 per cent of variance in awareness level and six variables i.e., personal cosmopolite sources use, social recognition, annual family income before and during pandemic and expenditure before and during pandemic explain 63.7 per cent variance of adaptation level. Rural people should be encouraged to participate in different extension activities. Findings would serve as a valid reference for researchers and policy makers concerning pandemic issues.